2014
DOI: 10.1111/crj.12194
|View full text |Cite
|
Sign up to set email alerts
|

Plasma miRNAs might be promising biomarkers of chronic obstructive pulmonary disease

Abstract: These results suggested that plasma miRNAs could be potential specific biomarker for early detection COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 37 publications
0
33
0
4
Order By: Relevance
“…(45) A recent report found that miR-145-5p is upregulated in plasma from asthma patients. (46) Thus, since recent reports suggest an increase in respiratory problems with personnel deployed to areas with open air burn pits (20) , one mechanism may include induction of miR-145-5p levels which can alter inflammatory gene responses and promote onset of respiratory diseases such as asthma. Likewise, miR-17-5p has been shown to be upregulated in various disease states including: pulmonary artery hypertension, hepatocellular carcinoma and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…(45) A recent report found that miR-145-5p is upregulated in plasma from asthma patients. (46) Thus, since recent reports suggest an increase in respiratory problems with personnel deployed to areas with open air burn pits (20) , one mechanism may include induction of miR-145-5p levels which can alter inflammatory gene responses and promote onset of respiratory diseases such as asthma. Likewise, miR-17-5p has been shown to be upregulated in various disease states including: pulmonary artery hypertension, hepatocellular carcinoma and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha evidenciado que los miR pueden expresarse de forma específica, ya sea por su presencia en un tejido o por aumento de su expresión en sangre periférica u otros fluidos corporales. De esta manera, los miR son secretados como microvesiculas hacia la circulación y por su gran estabilidad en tejidos y fluidos corporales, tienen potencial importante como marcadores diagnósticos (17) .…”
Section: Mecanismo De Acción Micro Arn (Mir)unclassified
“…Sin embargo, cabe señalar que los principales miR presentes en EPOC van a estar asociados a genes que regulan la inflamación, ya que es su mecanismo fisiopatológico principal (17,32) . En…”
Section: Micro Arn Y Epocunclassified
See 2 more Smart Citations